Pengaruh Work From Home Terhadap Produktivitas Melalui Motivasi Kerja Sebagai Moderasi ( Studi Pada Dinas Koperasi Usaha Mikro Dan Perdagangan Kota Batu) - Achmad Yani; Muhammad Mansur; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of work from home on productivity through work motivation as moderation. study on employees of the Batu City Micro Business and Trade Cooperative Office. The type of research used is quantitative research with the method of distributing questionnaires. The sample in this study were 55 respondents and data processing using the SPSS computer program. This research has met the validity and reliability requirements. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination analysis. The variables used in this study are the dependent variable Work From Home, while the independent variable is Productivity, and Work Motivation as a Moderating variable. The results of this study concluded that the moderating variable, namely Work Motivation, can strengthen the relationship between Work From Home and Productivity. Keywords: Work From Home, Productivity, And Work Motivation